Drag coefficient sonification in luge using a wind tunnel - Link, D.; Edelmann-Nusser, J. (International Journal of Sports Science and Engineering, 2012)
This paper describes a testing environment for luge that provides real time audio feedback to the athletes and presents findings from initial testing. The hardware is based on a wind tunnel, upon which an additional force plate and mount for the sledge were integrated. Determining the resistive forces in luge is sophisticated, because many interfering signals exist, e.g. stabili-zation movements of the athlete. Results show that it is difficult to repro-duce the drag coefficient to the second decimal place from trial to trial. As a consequence the central goal of wind tunnel training should not be to deter-mine the absolute optimum posture, but to create a feeling for good and bad movements on the sledge.